2016
DOI: 10.1155/2016/6304820
|View full text |Cite
|
Sign up to set email alerts
|

Returning for HIV Test Results: A Systematic Review of Barriers and Facilitators

Abstract: This systematic review aims to identify factors that facilitate or hinder the return for HIV test results. Four electronic databases were searched. Two independent reviewers selected eligible publications based on inclusion/exclusion criteria. Quantitative studies published since 1985 were included. Thirty-six studies were included in the final review. Individual level barriers included sociodemographic characteristics, such as being a male, of young age and low education level, risk behaviours such as injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Between 2004 and 2008, for example, 10% of Chileans who tested HIV positive failed to return to learn their HIV status (Irarrazábal et al, 2013;Mercurio, 2009). Such failures also have been reported in other countries (Ngangue et al, 2016;Wesolowskia et al, 2006). Currently, with the use of HIV rapid testing in primary care, this failure to return for the test results is expected to diminish.…”
Section: Introductionmentioning
confidence: 80%
“…Between 2004 and 2008, for example, 10% of Chileans who tested HIV positive failed to return to learn their HIV status (Irarrazábal et al, 2013;Mercurio, 2009). Such failures also have been reported in other countries (Ngangue et al, 2016;Wesolowskia et al, 2006). Currently, with the use of HIV rapid testing in primary care, this failure to return for the test results is expected to diminish.…”
Section: Introductionmentioning
confidence: 80%
“…In both countries, participants with low levels of education and literacy were less likely to receive HIV screening. Several studies have shown an association between education level and HIV testing among men in other countries [ 16 , 17 ]. Even though Cameroon is relatively wealthier than Chad, our results show that the participants´ wealth index was similar in both countries, at all levels.…”
Section: Discussionmentioning
confidence: 99%
“…These 2 phenomena might contribute to rendering this preventive strategy practically ineffective in such groups, as societal distinctions based on skin color, sex, social class, and sexual identity have become entrenched. [46] In fact, addressing such inequalities must be a priority in HIV prevention programs, once promoting access to most vulnerable populations has been a key challenge also to PrEP [47] and HIV testing, [48] globally.…”
Section: Discussionmentioning
confidence: 99%